Strategi Pengembangan UMKM dalam Meningkatkan Kesejahteraan Masyarakat di Kecamatan Tonra dalam Perspektif Maqāshid Syari’ah - Aldayanti, Aldayanti; Amir, Muhammad Fakhri; Muis, Musrini (HUMAN: South Asian Journal of Social Studies, 2024)
Abstrak. This study aims to determine the development strategy of UMKM in Tonra District and the effect of Maqāshid Syari'ah implementation in improving community welfare. This research uses qualitative research methods by using data collection techniques, namely field observation, interviews, and documentation. The data analysis technique used is data reduction, which presents the selected data as a whole and concludes the results of the data analysis obtained. The results of this study indicate that the development strategy of UMKM in Tonra District focuses on market development and product development. The utilization of social media and retail partnerships is a market development strategy used, while in product development the strategy used is to remain consistent with the taste of the product, the application of branding and maintaining product quality to increase competitiveness Despite facing challenges such as rising raw material prices and market competition, UMKM players find solutions by adjusting business capital and increasing creativity and reflecting the principles of Maqāshid Syari'ah and UMKM success. Regarding the effect of Maqāshid Syari'ah Implementation in UMKM in Tonra Sub-district, it has a positive impact on community welfare with wise financial management practices, fulfillment of spiritual obligations such as zakat, and economic empowerment through employment and technology. UMKM also reflects the principles of Maqāshid Syari’ah in maintaining religion, soul, mind, offspring, and property and creating a comprehensive impact on the welfa of the community and maintaining the sustainability and benefit of the people. Keywords: welfare, UMKM, Maqāshid syari'ah